2016
DOI: 10.3329/bjlr.v19i1-2.26423
|View full text |Cite
|
Sign up to set email alerts
|

Performance of BLRI developed native duck under farmer’s condition with supplementary feeding

Abstract: A total of 198 straight run day old ducklings of Bangladesh Livestock Research Institute (BLRI) developed native duck (named as Rupali and Nageswary) and local native duck genotypes were distributed among nine farmers of low laying areas of Kalihati Upazilla of Tangail district. Rupali and Nageswary ducklings were obtained from existing stock of BLRI and local native ducklings were collected from local farmers of the study area. After 12 weeks of age each farmers retained 10 female and 2 male ducks and sold aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
4
1
4
1
Order By: Relevance
“…The average egg weight was estimated as being 58.20 ± 1.50 g in the present study (Table 3). This result is in accordance with the findings of Khatun et al (2012) who reported average egg weight to be 57.22 ± 1.89 g in Nageswari ducks.…”
Section: Egg Weight and Laying Behaviorsupporting
confidence: 93%
See 3 more Smart Citations
“…The average egg weight was estimated as being 58.20 ± 1.50 g in the present study (Table 3). This result is in accordance with the findings of Khatun et al (2012) who reported average egg weight to be 57.22 ± 1.89 g in Nageswari ducks.…”
Section: Egg Weight and Laying Behaviorsupporting
confidence: 93%
“…This result is in accordance with the findings of Valavan et al (2009) who reported average annual egg production to be 200-220 in Nageswari duck under intensive management system. Khatun et al (2012) found 55.40 ± 2.36 % egg production rate up to 52 weeks of age in Nageswari duck which is relatively lower than the present study (60.19 ± 3.63) considering the same age of hen day egg production.…”
Section: Hen Day Egg Productioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Interaksi tanaman padi pada ternak itik adalah padi menyiapkan makanan pada ternak itik pada saat setelah panen yaitu dengan cara melepas itik di sawah yang telah dipanen dengan tujuan itik memakan sisa-sisa buah padi dan setelah pasca panen makanan itik bias didapat dari kulit buah padi yaitu dedak. (Lutfi, dkk., 2017 (Khatun, et al, 2012).…”
Section: Pola Pemeliharaan Itik Petelur DI Provinsi Sumatera Barat Khunclassified